Old Books, New Technologies - Marijke Crab, MC (Ciceroniana On Line)
The article introduces a postdoctoral research project entitled Cicero, Man of Letters. The Reception of Cicero’s Epistles in the Renaissance. Starting from a study of all Cicero letters editions printed in the fifteenth and sixteenth centuries, and the paratexts contained therein, this project seeks to establish not only which letters were published, when and where, by whom, for whom, in which language and why; but it also explores how these letters were read and interpreted in this period, and which image of Cicero they spread. In the present contribution, I describe how I went about collecting, organising and interpreting the source materials, with special attention to the methods followed, the digital resources used and the planned digital output, before presenting some intermediate results of my study of the Cicero letters editions printed up to 1550. Throughout, I highlight not only the prospects but also the limitations and possible pitfalls of these new technologies for studying old books.